A comparative study on fresh versus frozen embryo transfer at an infertility centre (Northern International Medical College Journal, 2025)
Background: The usage of frozen embryo transfer (FET) has been on the rise for the last few years, and it is a widely accepted technique of assisted reproductive technique (ART). Studies have compared the benefits of FET to fresh embryo transfer, including cost-effectiveness and maternal complications during in vitro fertilization (IVF). Aims of this study was to determine the pregnancy outcomes following fresh embryo transfer and FET and to find out whether FET results in better outcomes compared to fresh transfer. Methods: It was a cross-sectional study that took place at Hope Infertility Center, Dhaka, Bangladesh during the period of 2021-2023. 187 women candidates of IVF were divided into 2 groups of fresh (n = 106) and frozen (n = 81) embryo transfer. Demographic and clinical characteristics like age, BMI, cause and duration of infertility, number of IVF cycles and pregnancy outcomes like chemical and clinical pregnancy, ectopic pregnancy, abortion, intra uterine death (IUD), live birth were compared among these 2 groups. p < 0.05 was considered statistically significant. Results: No significant difference was observed between these groups in terms of age, cause and duration of infertility and number of IVF cycles. BMI (26.06±4.14 vs 27.44±5.05, p = 0.04) and live birth rates (13.21% vs 25.92%, p = 0.02) was significantly higher while, abortion (20.75% vs 9.88%, p = 0.04) was significantly lower in FET group compared to fresh embryo transfer group. Conclusion: In this study, it was shown that FET method increases the success rate of IVF. So, this study recommends that infertility treatment centers should prioritize the use of frozen methods over fresh methods.Northern International Medical College Journal Vol. 15 No. 1-2 July 2023-January 2024, Page 682-684